Analisis Bibliometrik dan Pemetaan Research Gap Emisi Gas Rumah Kaca pada Material Konstruksi Berkelanjutan Berbasis Data Scopus - Muhammad Irfansyah Bako; Aidil Azhar Sihotang Sihotang; Rafli ilhamdi nasution Nasution (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Ambon, 2026)
The increasing emissions of greenhouse gases (GHGs) have become a critical issue in global climate change, with the construction sector a major contributor due to material use and energy consumption throughout the building life cycle. This study aims to analyse the development of scientific literature, map the intellectual structure, and identify research gaps related to GHG emissions in sustainable construction materials using a quantitative bibliometric research approach. Secondary data were collected from the Scopus database, consisting of 1,968 documents published during the period 2000–2026 (adjust to the actual year range in your data), and analyzed using VOSviewer and bibliometrix (R). The results indicate that greenhouse gases serve as the central theme, strongly connected to key topics such as the construction industry, environmental impact, energy, construction materials, and waste management. The network visualisation reveals several major clusters that reflect the field's multidisciplinary nature, including energy and buildings, environmental and waste management, sustainable construction materials, and environmental impact assessment. However, the interconnections among these clusters remain relatively weak, particularly in integrating construction materials with life-cycle-based emission analysis through Life Cycle Assessment (LCA). These findings highlight significant opportunities for future research to develop more comprehensive and integrated approaches in assessing GHG emissions within the construction sector. This study contributes theoretically to the advancement of bibliometric research and provides a foundation for developing low-carbon materials and policy strategies to support sustainable development Keywords: Bibliometric analysis, Construction materials, Greenhouse gases, Sustainable construction, VOSviewer